WATER QUALITY IN A DISTURBED MINING LANDSCAPE, CZECH REPUBLIC - Vaštyl, Michal; Valová, Barbora; Vaňková, Barbara (GeoScience Engineering, 2018)
In this article, we assess the impact of the water flow system and precipitation on choosing hydro chemical parameter in water-bearing subside areas. Key findings of this study are significant correlation coefficient values obtained from the precipitation amount and occurrence of total phosphorus and phosphates. Therefore the significant effect of other anthropogenic activities on water reservoirs was excluded. The conclusion of this study is that inflowing water (in the case of relatively clean streams) and precipitation can have a positive influence on hydrochemical parameters in water-bearing subside areas and generally contribute to dilution. Keywords: water-bearing subside areas, precipitation, hydro chemical parameters https://doi.org/10.2478/gse-2018-0006